MOVES III. Simultaneous X-ray and ultraviolet observations unveiling the variable environment of the hot Jupiter HD 189733b. Issue 1 (29th January 2020) - Bourrier, V; Wheatley, P J; Lecavelier des Etangs, A; King, G; Louden, T; Ehrenreich, D; Fares, R; Helling, Ch; Llama, J; Jardine, M M; Vidotto, A A
ABSTRACT: In this third paper of the MOVES (Multiwavelength Observations of an eVaporating Exoplanet and its Star) programme, we combine Hubble Space Telescope far-ultraviolet (FUV) observations with XMM–Newton / Swift X-ray observations to measure the emission of HD 189733 in various FUV lines, and its soft X-ray spectrum. Based on these measurements we characterize the interstellar medium towards HD 189733 and derive semisynthetic XUV spectra of the star, which are used to study the evolution of its high-energy emission at five different epochs. Two flares from HD 189733 are observed, but we propose that the long-term variations in its spectral energy distribution have the most important consequences for the environment of HD 189733b. Reduced coronal and wind activity could favour the formation of a dense population of Si 2+ atoms in a bow-shock ahead of the planet, responsible for pre- and in-transit absorption measured in the first two epochs. In-transit absorption signatures are detected in the Lyman α line in the second, third, and fifth epochs, which could arise from the extended planetary thermosphere and a tail of stellar wind protons neutralized via charge-exchange with the planetary exosphere. We propose that increases in the X-ray irradiation of the planet, and decreases in its EUV irradiation causing lower photoionization rates of neutral hydrogen, favour the detection of these signatures by sustaining larger densities of H 0 atoms in the upper atmosphere and boosting charge-exchanges with the stellar wind. Deeper and broader absorption signatures in the last epoch suggest that the planet entered a different evaporation regime, providing clues as to the link between stellar activity and the structure of the planetary environment.